Electrical Machines - Ghosh, Samarjit (India : Pearson Education, 2007)
Engineering
2011-06-23
Keywords: Electrics; Electric Machines; Electromagnetism; Magnetic Circuit; Roating Machines; Transformer; DC Generator; DC Motors; AC Motor Control